Increased Fiber Intake Enhances Clostridia Bacteria and Reduces Clinical Relapse in Patients With Clinically Quiescent Inflammatory Bowel Disease: A Prospective Longitudinal Study - Julajak Limsrivilai; Phalat Sathirawich; Onuma Sattayalertyanyong; Pornpoj Pramyothin; Iyarit Thaipisuttikul; Nonthalee Pausawasdi; Phunchai Charatcharoenwitthaya; Rungnapha Sarasak; Perapon Nitayanon; Phutthaphorn Phaophu; Nichcha Subdee; Sathaporn Manatsathit (JGH Open, 2025)
ABSTRACT Background and Aim A high‐fiber, low‐animal‐protein, and low‐saturated‐fat diet may modulate gut dysbiosis and benefit inflammatory bowel disease (IBD). This study investigated the effects of this diet on clinical relapses, fecal calprotectin, and gut microbiota in patients with clinically quiescent IBD. Methods Sixty‐one patients with IBD were enrolled (23 Crohn's disease and 38 ulcerative colitis). All patients were in clinical remission and had maintained unchanged treatment for at least 2 months. They were advised to increase fiber intake and decrease animal protein and saturated fat consumption. Assessments were performed at baseline, week 6, and every 12 weeks until flare or study completion at 54 weeks. Fecal calprotectin and microbiota were analyzed at baseline and upon study completion. The effect of each dietary component on outcomes was analyzed separately. Results The cumulative flare rate was 22.6%. Increased fiber intake was significantly associated with a lower incidence of clinical flares. Flare rates were 12.6%, 20.5%, and 46.5% in the increased, unchanged, and decreased fiber intake groups, respectively, with significant differences between the increased and decreased groups (p = 0.03). Fecal calprotectin, however, was not significantly different in those who increased fiber intake compared to those who did not. Microbiota analysis showed a significant increase in the Clostridia class in the increased fiber intake group. Conclusions Increasing dietary fiber increased Clostridia class bacteria and was associated with a longer time to flare in patients with clinically quiescent IBD.